2023
DOI: 10.31219/osf.io/y2phs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of aerobic exercise on hippocampal formation volume in people with schizophrenia – a systematic review and meta-analysis with original data from a randomized-controlled trial

Abstract: Background: Aerobic exercise is a promising add-on treatment to counteract structural and functional impairments of the hippocampal formation and associated clinical outcome in schizophrenia. However, current evidence regarding exercise effects on the hippocampal formation in patients with schizophrenia is still limited and inconclusive. Therefore, we aim to assess the impact of aerobic exercise on the volume and connectivity of the hippocampal formation and explore the clinical relevance of potential exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Therefore, the utmost investigated brain region is the hippocampus, together with its subfields and the parahippocampal areas. Volumetric studies reported mixed results consequent to aerobic fitness, with evidences for either an increased cortical volume of the hippocampus in schizophrenic patients [ 25 , 27 , 30 , 35 , 39 ] or stable hippocampal grey matter both in clinical high-risk subjects [ 23 , 24 ] and later stages of psychosis [ 31 , 36 , 37 ]. The same pattern is found also while looking at the hippocampal subfields, with Damme et al [ 23 ] reporting a negative correlation of its volume in the absence of aerobic activity and Maurus et al [ 25 ] reporting an increased volume associated with physical activity; whereas Malchow et al [ 31 ] describe no structural changes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the utmost investigated brain region is the hippocampus, together with its subfields and the parahippocampal areas. Volumetric studies reported mixed results consequent to aerobic fitness, with evidences for either an increased cortical volume of the hippocampus in schizophrenic patients [ 25 , 27 , 30 , 35 , 39 ] or stable hippocampal grey matter both in clinical high-risk subjects [ 23 , 24 ] and later stages of psychosis [ 31 , 36 , 37 ]. The same pattern is found also while looking at the hippocampal subfields, with Damme et al [ 23 ] reporting a negative correlation of its volume in the absence of aerobic activity and Maurus et al [ 25 ] reporting an increased volume associated with physical activity; whereas Malchow et al [ 31 ] describe no structural changes.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the vast majority of functional studies based their hypotheses on previous structural findings and aimed at shining new light on hippocampal changes consequent to exercise training by looking at its functional connectivity [ 23 , 24 , 27 , 32 ]. Functional connectivity of the hippocampus seemed to increase with the occipital lobe after physical exercise both in ultra-high risks subjects for psychosis [ 24 ] and in attenuated forms of psychosis [ 23 ] compared to control conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations